Crisis de los imperios ibéricos y conexiones transatlánticas - Marcela Ternavasio (Casa de Velázquez, 2021)
This article analyses the transatlantic plots in which the Portuguese occupation of the Banda Oriental of Río de la Plata took place and the effects it provoked both in the new concert of powers that emerged from the Restoration and in the tensions that crossed the Iberian world, with special attention to the representations that were elaborated in the previous seat of the Portuguese monarchy installed in Brazil. Through Ricardo Raimundo Nogueira's Memorias Políticas and a varied corpus of documents, the text reflects on two relevant historiographical issues: the reconfiguration of the links between war, politics and diplomacy, and the different conceptions that Spain and Portugal projected regarding the imperial question and the future drift of their monarchies.